Studi Komparatif Terhadap Hukum Penyucian Kulit Bangkai Dengan Cara Disamak Menurut Ibnu Qudamah Al-Maqdisi dan Imam Asy-Syaukani - Siti Nuryana; Legawan Isa; Ikhwan Fikri (Muqaranah, 2023)
This article discusses the law on the utilization of animal carcass skins after going through the tanning process. The main issues to be analyzed are: the views of Ibn Qudamah Al-Maqdisi and Imam Asy Syaukani regarding the law of purifying carcass skins by tanning; the similarities and differences of opinions regarding purifying carcass skins by tanning according to Ibn Qudamah Al-Maqdisi and Imam Asy-Syaukani. The purpose of this study is to find out the views of Ibn Qudamah Al-Maqdisi and Imam Asy Syaukani and the similarities and differences regarding the law of purifying animal carcasses by tanning them. This research uses the type of research Library Research, with qualitative research methods. In data collection techniques, the author uses secondary data, namely the book Al-Mughni Volume 1 by Ibnu Qudamah Al-Maqdisi and the book Nailul Authar Volume 1 by Imam Asy-Syaukani then these data will be compared descriptively comparatively. After going through a comparative analysis process, that the views of Ibn Qudamah Al-Maqdisi and Imam Asy-Syaukani have different views regarding the purity of animal carcass skins after being tanned, according to Ibn Qudamah Al-Maqdisi, animal carcass skins both after and before being tanned cannot become holy so they cannot be the skin is used, while Imam Asy-Syaukani believes that after going through the tanning process, the carcass skin can become holy and its uses can be utilized.